Touch screen glass panel and manufacturing method

By plating ITO film on the touch screen glass panel and spraying modified paint to form a protective layer, the problem of easy stains and poor fingerprint resistance of the panel is solved, and a comprehensive improvement of high water contact angle, oil contact angle and fingerprint resistance is achieved.

CN119752324BActive Publication Date: 2025-05-02TIANJIN SHIYU ELECTRONICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510258549.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-05-02
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

The touch screen glass panel is prone to stains of water and oil in daily use, and has poor anti-fingerprint performance, which affects the visual effect and operation accuracy.

Method used

By magnetron sputtering on the surface of the coated glass substrate and spraying modified coatings to form a protective layer, the water contact angle, oil contact angle and fingerprint resistance of the glass panel are improved. The modified coating consists of tetraethyl silicate, 1,2-bistrimethoxysilylethane, 2-perfluorooctylethyl alcohol and fluoro-containing silane. The siloxane network structure is formed through hydrolysis and condensation reaction, which enhances hydrophobicity and barrier properties.

Benefits of technology

It realizes the excellent light transmittance, hardness, water contact angle, oil contact angle and fingerprint resistance of the touch screen glass panel, which significantly improves the user experience and the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention discloses a touch screen glass panel and a manufacturing method, which belongs to the technical field of glass panel production. The touch screen glass panel includes a glass substrate, an ITO thin film is magnetron sputtered on the surface of the glass substrate to obtain a coated glass substrate, and a modified coating is coated on the surface of the coated glass substrate to obtain a touch screen glass panel. After testing, the touch screen glass panel manufactured by the present invention has excellent light transmittance (95.1% to 95.5%), hardness (Mohs hardness reaches 7), water contact angle (104.2° to 105.4°), oil contact angle (86.1° to 87.2°) and anti-fingerprint performance (RFU value reaches 77 to 82), and the comprehensive performance is significantly improved. Further, after testing, the protective layer formed by the modified coating added with the fluorine-containing silane prepared by the present invention has excellent bonding performance with the coated glass substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of glass panel production, and in particular relates to a touch screen glass panel and a manufacturing method thereof. Background Art

[0002] Touch screen glass panels have become an indispensable key component of various electronic devices. With the evolution of technology, glass manufacturers have improved the light transmittance and Mohs hardness of glass by optimizing glass formula and processing technology to meet the needs of electronic devices for display clarity and scratch resistance.

[0003] However, as people's requirements for the user experience of electronic devices continue to increase, touch screen glass panels face new challenges. In daily use, touch screen glass panels frequently come into contact with substances such as fingers, sweat, and grease. Since the water contact angle and oil contact angle of traditional glass panels are small, water and oil can easily spread on their surfaces, causing the screen surface to be easily stained, which not only affects the visual effect but also requires frequent wiping. At the same time, ordinary glass panels have poor anti-fingerprint performance, and fingerprint traces are seriously residual, which not only affects the appearance, but may also interfere with the accuracy of touch operations.

[0004] In order to improve user experience, improving the water contact angle, oil contact angle and anti-fingerprint performance of the touch screen glass panel has become an urgent problem to be solved. Summary of the invention

[0005] The object of the present invention is to provide a touch screen glass panel and a manufacturing method thereof, so as to improve the water contact angle, oil contact angle and anti-fingerprint performance of the touch screen glass panel.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A touch screen glass panel comprises a glass substrate;

[0008] An ITO thin film is coated on the surface of the glass substrate by magnetron sputtering to obtain a coated glass substrate;

[0009] The surface of the coated glass substrate is coated with a modified coating to obtain a touch screen glass panel;

[0010] The modified coating is prepared by the following steps:

[0011] A1. Fill anhydrous ethanol with nitrogen for protection, then add 3-aminopropyltriethoxysilane and 2H,2H-perfluorooctanal thereto with stirring, add p-toluenesulfonic acid thereto after stirring and mixing, heat to 40-50°C, stir at constant temperature for 8-12h, cool to room temperature, remove ethanol to obtain a crude product, separate and purify the crude product by column chromatography, elute with eluent, and rotary evaporate to obtain fluorine-containing silane. The preparation process is as follows:

[0012] .

[0013] A2. Mix tetraethyl silicate, 1,2-bistrimethoxysilylethane and 2-perfluorooctylethyl alcohol, stir and heat to 40-45°C, then add 36% hydrochloric acid solution by mass and stir to adjust the pH of the system to 4.5-5.0. After completion, add pure water and fluorine-containing silane after mixing and stirring, heat to 50°C, stir at constant temperature for 12 hours, then distill under reduced pressure, add methyl-1,1,2,2-tetrafluoroethyl ether to dilute to a solid content of 3.5%-4.0%, then add dibutyltin diacetate and stir for 1-2 hours to obtain a modified coating.

[0014] Furthermore, the dosage ratio of anhydrous ethanol, 3-aminopropyltriethoxysilane and 2H,2H-perfluorooctanal in A1 is 500mL:0.1mol:0.1~0.11mol; the dosage of p-toluenesulfonic acid in A1 is 2~5mol% of the total molar amount of 3-aminopropyltriethoxysilane and 2H,2H-perfluorooctanal.

[0015] Furthermore, the column chromatography described in A1 is a silica gel column; the eluent described in A1 is prepared by a volume ratio of n-hexane:ethyl acetate=5:1.

[0016] Furthermore, the dosage ratio of tetraethyl silicate, 1,2-bistrimethoxysilylethane, 2-perfluorooctylethyl alcohol, pure water and fluorine-containing silane compound in A2 is 1g:2.8~3.0g:10g:10mL:0.54~0.55g; the dosage of dibutyltin diacetate in A2 is 0.5%~1.0% of the total mass of the mixed solution.

[0017] Furthermore, a method for manufacturing a touch screen glass panel comprises the following steps:

[0018] S1. Mix glass substrate raw materials and place them in a high-temperature furnace for melting. The furnace temperature is 1450-1540° C. and the melting time is 4-5 hours. After completion, a glass liquid is formed. The glass liquid is then clarified. The clarification temperature is 1550-1650° C. and the clarification time is 2-3 hours. After completion, a clarified glass liquid is obtained. The clarified glass liquid is floated on molten tin liquid. The tin liquid temperature is controlled at 1000-1100° C. and the time is controlled at 4-5 minutes. Under the action of gravity and surface tension, the clarified glass liquid is formed into a substrate-shaped glass. The substrate-shaped glass is then annealed and cooled to obtain a glass substrate.

[0019] S2, subjecting the preheated glass substrate to magnetron sputtering coating, selecting an ITO target material with a purity of 99.99% as a target material, coating an ITO thin film on the glass substrate, cooling it to room temperature, and then annealing it at 320-350° C. for 1.5-2 hours to obtain a coated glass substrate;

[0020] S3, spraying the modified coating on the coated side of the cleaned and dried coated glass substrate to form a protective layer, and then curing and drying to obtain a touch screen glass panel.

[0021] Furthermore, the glass substrate in S1 comprises the following raw materials in parts by mass: 62-65 parts of SiO2, 10-15 parts of Na2O, 8-12 parts of Al2O3, 1-3 parts of B2O3, 2-5 parts of K2O, 4-5 parts of MgO, and 3-5 parts of CaO.

[0022] Furthermore, the temperature of the annealing treatment in S1 is 580-650° C., and the annealing time is 12 hours.

[0023] Furthermore, the thickness of the glass substrate in S1 is 0.85-1.1 mm.

[0024] Furthermore, the conditions for magnetron sputtering described in S2 are: the working gas is argon gas with a purity of 99.999%, the argon gas flow rate is controlled to be 10-100 sccm, and the vacuum degree is 1×10 -3 ~1×10 -4 Pa, the sputtering power is 300-400W, and the sputtering speed is 1.5nm / min.

[0025] Furthermore, the thickness of the ITO film in S2 is 100 nm.

[0026] Furthermore, the thickness of the protective layer in S3 is 50-100 nm.

[0027] Beneficial effects of the present invention:

[0028] The present invention provides a touch screen glass panel and a manufacturing method thereof, wherein the touch screen glass panel provided by the present invention is composed of a glass substrate, a touch sensing layer and a protective layer. After testing, the touch screen glass panel manufactured by the present invention has excellent light transmittance (95.1% to 95.5%), hardness (Mohs hardness reaches 7), water contact angle (104.2° to 105.4°), oil contact angle (86.1° to 87.2°) and anti-fingerprint performance (RFU value reaches 77 to 82), and the comprehensive performance is significantly improved, and the reasons are as follows:

[0029] Firstly, the present invention forms a protective layer on the surface of the coated glass substrate by spraying the modified coating, and the thickness of the protective layer is 50 to 100 nm. The existence of the protective layer can effectively prevent the intrusion of water and oil and reduce the adhesion of stains on the surface; at the same time, the spraying method can provide good surface flatness, which helps to reduce the adverse effects of surface roughness on the contact angle.

[0030] Then, in the modified coating of the present invention, tetraethyl silicate and 1,2-bistrimethoxysilylethane undergo hydrolysis and condensation reaction under acidic conditions to form a siloxane network structure, which provides a good dispersion and fixation environment for fluorine-containing silane, so that the fluorine-containing component can be evenly distributed in the protective layer; at the same time, the siloxane network structure itself also has stability and barrier properties, which can prevent the penetration of water and oil, and further improve the anti-fouling performance of the touch screen glass panel; and, in the modified coating, 2-perfluorooctylethyl alcohol is used as a solvent, and the fluoroalkyl group contained in it helps to guide the fluorine-containing groups to migrate to the surface of the formed protective layer during the drying and film-forming process of the coating, thereby enriching more fluorine elements on the surface, so that the fluorine content on the surface of the protective layer is relatively increased, further reducing the surface energy, and enhancing the hydrophobicity and oleophobicity of the protective layer.

[0031] Next, in the preparation process of the fluorinated silane in the modified coating, 3-aminopropyltriethoxysilane and 2H,2H-perfluorooctanal react to generate fluorinated silane. The introduction of fluorine atoms from perfluorooctanal makes the fluorinated silane have a lower surface energy. The fluorine atoms have strong electronegativity and the bond energy of the CF bond is high. This structure makes the material surface have extremely low affinity for water and oil. According to the principles of surface chemistry, materials with low surface energy can make water and oil form a larger contact angle on their surface, thereby increasing the water contact angle and the oil contact angle.

[0032] Furthermore, it has been found that the protective layer formed by the modified coating containing the fluorine-containing silane prepared in the present invention has excellent bonding performance with the coated glass substrate for the following reasons:

[0033] The fluorine-containing silane prepared by the present invention contains a Schiff base structure, and the indium ions and tin ions on the surface of the coated glass substrate have empty valence orbitals and can accept electron pairs. When the modified coating containing the Schiff base structure is sprayed on the surface of the coated glass substrate, the nitrogen atoms in the Schiff base will provide their lone pairs of electrons to the empty orbitals of the indium and tin ions to form coordination bonds, thereby enhancing the bonding performance between the protective layer formed by the modified coating and the coated glass substrate. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] Preparation of modified coatings:

[0037] First, fluorinated silane was prepared: anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) was added to reactor A, nitrogen was filled in for protection, and then 3-aminopropyltriethoxysilane (97.0%; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 2H,2H-perfluorooctanal (97%; purchased from Changzhou Xinfu Chemical Co., Ltd.) were added to reactor A with stirring, wherein the amount ratio of anhydrous ethanol, 3-aminopropyltriethoxysilane and 2H,2H-perfluorooctanal was 500mL:0.1mol:0.1mol. After the addition was completed, the mixture was stirred at room temperature for 5 minutes, and then 3-aminopropyltriethoxysilane and a catalyst of 2 mol% of the total molar amount of 2H,2H-perfluorooctanal, p-toluenesulfonic acid (99%; purchased from Changzhou Xinfu Chemical Co., Ltd.) were added to reactor A with stirring. The catalyst p-toluenesulfonic acid is purchased from Sinopharm Chemical Reagent Co., Ltd. The role of the catalyst p-toluenesulfonic acid is to make the carbonyl group of the aldehyde group more polarized, enhance its electrophilicity, and promote the nucleophilic attack of the amino group, thereby accelerating the reaction rate. After the addition is completed, the reactor A is heated to 40°C and stirred at a constant temperature for 8 hours. After the reaction is completed, it is cooled to room temperature, and then the solvent ethanol is removed under reduced pressure using a rotary evaporator to obtain a crude product. The crude product is then separated and purified by column chromatography. A silica gel column is selected for column chromatography, and an eluent is prepared according to a volume ratio of n-hexane: ethyl acetate = 5:1 to elute the silica gel column. Among them, n-hexane and ethyl acetate are purchased from Sinopharm Chemical Reagent Co., Ltd. After the elution is completed, the eluent is collected, and then a rotary evaporator is used to remove excess solvent n-hexane and ethyl acetate to obtain fluorinated silane.

[0038] Then prepare the modified coating: add tetraethyl silicate (TEOS, 99.99% purity, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.), 1,2-bistrimethoxysilylethane (95%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) and solvent 2-perfluorooctylethyl alcohol (purchased from Fuxin Hengtong Fluorine Chemical Co., Ltd.) into reactor B in a mass ratio of 1:2.8:10. After the addition is completed, mix and stir for 20 minutes. Heat the reactor B to 40°C, and then stir and add a 36% hydrochloric acid solution (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) to adjust the pH of the system to 4.5. After the adjustment is completed, mix and stir for 20 minutes. After completion, add the reactor B to the reactor B. Pure water and fluorine-containing silane were added to reactor B with stirring, wherein, with tetraethyl silicate as a reference ratio, the amount ratio of pure water, fluorine-containing silane compound and tetraethyl silicate was 10 mL: 0.54 g: 1 g. After the addition was completed, the temperature of reactor B was raised to 50° C. and the reaction was stirred at a constant temperature for 12 hours. After completion, the pure water was removed by distillation under reduced pressure, and then the solvent methyl-1,1,2,2-tetrafluoroethyl ether (purchased from Fuxin Hengtong Fluorine Chemical Co., Ltd.) was added thereto with stirring to dilute to a solid content of 3.5% to form a mixed solution, and then 0.5% of the total mass of the mixed solution dibutyltin diacetate (95%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) was added to the mixed solution with stirring, and the mixture was mixed and stirred for 1 hour. After completion, a modified coating was obtained.

[0039] Example 2

[0040] Preparation of modified coatings:

[0041] First, fluorinated silane was prepared: anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) was added to reactor A, nitrogen was filled in for protection, and then 3-aminopropyltriethoxysilane (97.0%; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 2H,2H-perfluorooctanal (97%; purchased from Changzhou Xinfu Chemical Co., Ltd.) were added to reactor A with stirring, wherein the amount ratio of anhydrous ethanol, 3-aminopropyltriethoxysilane and 2H,2H-perfluorooctanal was 500mL:0.1mol:0.11mol. After the addition was completed, the mixture was stirred at room temperature for 30 minutes, and then 3-aminopropyltriethoxysilane and a catalyst of 5 mol% of the total molar amount of 2H,2H-perfluorooctanal (99%; The catalyst p-toluenesulfonic acid is used to polarize the carbonyl group of the aldehyde group, enhance its electrophilicity, and promote the nucleophilic attack of the amino group, thereby accelerating the reaction rate. After the addition is completed, the reactor A is heated to 45°C and stirred at a constant temperature for 12 hours. After the reaction is completed, it is cooled to room temperature, and then the solvent ethanol is removed under reduced pressure using a rotary evaporator to obtain a crude product. The crude product is then separated and purified by column chromatography. A silica gel column is used for column chromatography, and an eluent is prepared according to a volume ratio of n-hexane: ethyl acetate = 5:1 to elute the silica gel column. Among them, n-hexane and ethyl acetate are purchased from Sinopharm Chemical Reagent Co., Ltd. After the elution is completed, the eluent is collected, and then a rotary evaporator is used to remove excess solvent n-hexane and ethyl acetate to obtain fluorinated silane.

[0042] Then, the modified coating was prepared: tetraethyl silicate (TEOS, 99.99% purity, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.), 1,2-bistrimethoxysilylethane (95%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) and solvent 2-perfluorooctylethyl alcohol (purchased from Fuxin Hengtong Fluorine Chemical Co., Ltd.) were added to the reactor B in a mass ratio of 1:2.9:10. After the addition was completed, the mixture was stirred for 30 minutes. The reactor B was heated to 45°C, and a 36% hydrochloric acid solution (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) was added thereto with stirring to adjust the pH of the system to 4.8. After the adjustment was completed, the mixture was stirred for 30 minutes. After completion, the reactor B was heated to 45°C, and a 36% hydrochloric acid solution (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) was added thereto with stirring to adjust the pH of the system to 4.8. After the adjustment was completed, the mixture was stirred for 30 minutes. After completion, the reactor B was heated to 45°C, and the mixture was stirred to 45°C. Pure water and fluorine-containing silane were added to reactor B with stirring, wherein tetraethyl silicate was used as a reference ratio, and the amount ratio of pure water, fluorine-containing silane compound and tetraethyl silicate was 10 mL: 0.55 g: 1 g. After the addition was completed, the temperature of reactor B was raised to 50° C. and the reaction was stirred at a constant temperature for 12 hours. After the completion, the pure water was removed by distillation under reduced pressure, and then the solvent methyl-1,1,2,2-tetrafluoroethyl ether (purchased from Fuxin Hengtong Fluorine Chemical Co., Ltd.) was added thereto with stirring to dilute to a solid content of 3.8% to form a mixed solution, and then 1.0% of the total mass of the mixed solution dibutyltin diacetate (95%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) was added to the mixed solution with stirring, and the mixture was mixed and stirred for 2 hours. After the completion, a modified coating was obtained.

[0043] Example 3

[0044] Preparation of modified coatings:

[0045] First, fluorinated silane was prepared: anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) was added to reactor A, nitrogen was filled in for protection, and then 3-aminopropyltriethoxysilane (97.0%; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 2H,2H-perfluorooctanal (97%; purchased from Changzhou Xinfu Chemical Co., Ltd.) were added to reactor A with stirring, wherein the amount ratio of anhydrous ethanol, 3-aminopropyltriethoxysilane and 2H,2H-perfluorooctanal was 500mL:0.1mol:0.11mol. After the addition was completed, the mixture was stirred at room temperature for 30 minutes, and then 3-aminopropyltriethoxysilane and a catalyst of 5 mol% of the total molar amount of 2H,2H-perfluorooctanal (99%; The catalyst p-toluenesulfonic acid is used to polarize the carbonyl group of the aldehyde group, enhance its electrophilicity, and promote the nucleophilic attack of the amino group, thereby accelerating the reaction rate. After the addition is completed, the reactor A is heated to 50°C and stirred at a constant temperature for 12 hours. After the reaction is completed, it is cooled to room temperature, and then the solvent ethanol is removed under reduced pressure using a rotary evaporator to obtain a crude product. The crude product is then separated and purified by column chromatography. A silica gel column is used for column chromatography, and an eluent is prepared according to a volume ratio of n-hexane: ethyl acetate = 5:1 to elute the silica gel column. Among them, n-hexane and ethyl acetate are purchased from Sinopharm Chemical Reagent Co., Ltd. After the elution is completed, the eluent is collected, and then a rotary evaporator is used to remove excess solvent n-hexane and ethyl acetate to obtain fluorinated silane.

[0046] Then prepare the modified coating: add tetraethyl silicate (TEOS, 99.99% purity, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.), 1,2-bistrimethoxysilylethane (95%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) and solvent 2-perfluorooctylethyl alcohol (purchased from Fuxin Hengtong Fluorine Chemical Co., Ltd.) into reactor B in a mass ratio of 1:3.0:10. After the addition is completed, mix and stir for 30 minutes. Heat the reactor B to 45°C, and then stir and add a 36% hydrochloric acid solution (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) to adjust the pH of the system to 5.0. After the adjustment is completed, mix and stir for 30 minutes. After completion, add the reactor B to the reactor B. Pure water and fluorine-containing silane were added to reactor B with stirring, wherein tetraethyl silicate was used as a reference ratio, and the amount ratio of pure water, fluorine-containing silane compound and tetraethyl silicate was 10 mL: 0.55 g: 1 g. After the addition was completed, the temperature of reactor B was raised to 50° C. and the reaction was stirred at a constant temperature for 12 hours. After the completion, the pure water was removed by distillation under reduced pressure, and then the solvent methyl-1,1,2,2-tetrafluoroethyl ether (purchased from Fuxin Hengtong Fluorine Chemical Co., Ltd.) was added thereto with stirring to dilute to a solid content of 4.0% to form a mixed solution, and then 1.0% of the total mass of the mixed solution dibutyltin diacetate (95%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) was added to the mixed solution with stirring, and the mixture was mixed and stirred for 2 hours. After the completion, a modified coating was obtained.

[0047] Comparative Example 1

[0048] Comparative Example 1 is the control group of Example 2, in which the fluorinated silane in the modified coating prepared in Example 2 is replaced with perfluorooctyltriethoxysilane (purchased from Sichuan Shangfu Technology Co., Ltd.), and the remaining raw materials, raw material amounts and preparation steps are consistent with Example 2, and finally a modified coating is obtained.

[0049] Example 4

[0050] A method for manufacturing a touch screen glass panel comprises the following steps:

[0051] Preparation of glass substrate: First, weigh the following raw materials according to mass: 62 parts of SiO2, 10 parts of Na2O, 8 parts of Al2O3, 1 part of B2O3, 2 parts of K2O, 4 parts of MgO, and 1 part of CaO. 3 parts, the raw materials are mixed and placed in a high-temperature furnace for melting, the furnace temperature is 1450°C, the melting time is 4h, so that the raw materials are fully melted and mixed evenly, after melting, glass liquid is formed, and then the glass liquid is clarified, the clarification temperature is 1550°C, the clarification time is 2h, after the glass liquid is melted, there will be many bubbles in it, these bubbles will affect the quality of the glass, the clarification process is to eliminate these bubbles, after clarification, clarified glass liquid is obtained, the clarified glass liquid is formed into flat glass by float process, the float process is to float the clarified glass liquid on the molten tin liquid, the tin liquid temperature is controlled at 1000°C, the time is controlled at 4min, under the action of gravity and surface tension, the clarified glass liquid is formed into a flat substrate-shaped glass, and then the produced substrate-shaped glass is annealed, the annealing temperature is 580°C, the annealing time is 12h, after annealing, it is cooled to room temperature to obtain a glass substrate, the thickness of the glass substrate is 0.85mm;

[0052] Preparation of touch sensing layer: First, the glass substrate was preheated at 170 °C for 20 min. The purpose of preheating was to remove the trace water vapor remaining on the surface of the glass substrate and to improve the activity of the surface of the glass substrate, which was beneficial to the subsequent adhesion of the ITO film. After preheating, the glass substrate was transferred to the sputtering chamber, and an ITO target with a purity of 99.99% (indium tin oxide, In2O3:SnO2=90:10; purchased from Zhuzhou Torch Antai New Materials Co., Ltd.) was selected as the magnetron sputtering target. The working gas was argon with a purity of 99.999%, the argon flow rate was controlled to 10 sccm, and the vacuum degree was 1×10 -3 Pa, sputtering power of 300W, sputtering speed of 1.5nm / min, a 100nm thick ITO film is plated on a glass substrate, then cooled to room temperature, and then annealed at 320℃ for 1.5h. During the annealing process, the crystal structure of the film will be further optimized, the resistivity of the film will be reduced, and its transparency will be improved. After annealing, a coated glass substrate is obtained;

[0053] Preparation of a protective layer: First, the coated glass substrate is ultrasonically cleaned in anhydrous ethanol, and then dried in a 40°C constant temperature drying oven for 12 hours. After completion, the modified coating prepared in Example 1 is sprayed on the coated side of the coated glass substrate to form a protective layer. The thickness of the protective layer is controlled at 50 nm. After spraying, it is placed in an 80°C constant temperature drying oven for curing for 80 minutes, and then stored in a dry environment for 24 hours. After completion, a touch screen glass panel is obtained.

[0054] Example 5

[0055] A method for manufacturing a touch screen glass panel comprises the following steps:

[0056] Preparation of glass substrate: First, weigh the following raw materials according to mass: 64 parts of SiO2, 12 parts of Na2O, 10 parts of Al2O3, 2 parts of B2O3, 4 parts of K2O, 4 parts of MgO, and 10 parts of CaO. 3 parts, the raw materials are mixed and placed in a high-temperature furnace for melting, the furnace temperature is 1500℃, the melting time is 5h, so that the raw materials are fully melted and mixed evenly, after melting, glass liquid is formed, and then the glass liquid is clarified, the clarification temperature is 1600℃, the clarification time is 3h, after the glass liquid is melted, it will contain many bubbles, these bubbles will affect the quality of the glass, the clarification process is to eliminate these bubbles, after clarification, clarified glass liquid is obtained, the clarified glass liquid is formed into flat glass by float process, the float process is to float the clarified glass liquid on the molten tin liquid, the tin liquid temperature is controlled at 1050℃, the time is controlled at 5min, under the action of gravity and surface tension, the clarified glass liquid is formed into a flat substrate-shaped glass, and then the produced substrate-shaped glass is annealed, the annealing temperature is 620℃, the annealing time is 12h, after annealing, it is cooled to room temperature to obtain a glass substrate, the thickness of the glass substrate is 1.0mm;

[0057] Preparation of touch sensing layer: First, the glass substrate was preheated at 180 °C for 30 min. The purpose of preheating was to remove the trace amount of water vapor remaining on the surface of the glass substrate and to improve the activity of the surface of the glass substrate, which was beneficial to the subsequent adhesion of the ITO film. After preheating, the glass substrate was transferred to the sputtering chamber, and an ITO target with a purity of 99.99% (indium tin oxide, In2O3:SnO2=90:10; purchased from Zhuzhou Torch Antai New Materials Co., Ltd.) was selected as the magnetron sputtering target. The working gas was argon with a purity of 99.999%, the argon flow rate was controlled to 100 sccm, and the vacuum degree was 1×10 -4 Pa, sputtering power of 350W, sputtering speed of 1.5nm / min, a 100nm thick ITO film is plated on a glass substrate, then cooled to room temperature, and then annealed at 320℃ for 2h. During the annealing process, the crystal structure of the film will be further optimized, the resistivity of the film will be reduced, and its transparency will be improved. After annealing, a coated glass substrate is obtained;

[0058] Preparation of protective layer: First, the coated glass substrate is ultrasonically cleaned in anhydrous ethanol, and then placed in a 40°C constant temperature drying oven for drying for 12 hours. After completion, the modified coating prepared in Example 2 is sprayed on the coated side of the coated glass substrate to form a protective layer. The thickness of the protective layer is controlled at 100 nm. After spraying, it is placed in an 80°C constant temperature drying oven for curing for 100 minutes, and then stored in a dry environment for 24 hours. After completion, a touch screen glass panel is obtained.

[0059] Example 6

[0060] A method for manufacturing a touch screen glass panel comprises the following steps:

[0061] Preparation of glass substrate: First, weigh the following raw materials according to mass: 65 parts of SiO2, 15 parts of Na2O, 12 parts of Al2O3, 3 parts of B2O3, 5 parts of K2O, 5 parts of MgO, and 5 parts of CaO. 5 parts, the raw materials are mixed and placed in a high-temperature furnace for melting, the furnace temperature is 1540℃, the melting time is 5h, so that the raw materials are fully melted and mixed evenly, after melting, glass liquid is formed, and then the glass liquid is clarified, the clarification temperature is 1650℃, the clarification time is 3h, after the glass liquid is melted, it will contain many bubbles, these bubbles will affect the quality of the glass, the clarification process is to eliminate these bubbles, after clarification, clarified glass liquid is obtained, the clarified glass liquid is formed into flat glass by float process, the float process is to float the clarified glass liquid on the molten tin liquid, the tin liquid temperature is controlled at 1100℃, the time is controlled at 5min, under the action of gravity and surface tension, the clarified glass liquid is formed into a flat substrate-shaped glass, and then the produced substrate-shaped glass is annealed, the annealing temperature is 650℃, the annealing time is 12h, after annealing, it is cooled to room temperature to obtain a glass substrate, the thickness of the glass substrate is 1.1mm;

[0062] Preparation of touch sensing layer: First, the glass substrate was preheated at 180 °C for 30 min. The purpose of preheating was to remove the trace amount of water vapor remaining on the surface of the glass substrate and to improve the activity of the surface of the glass substrate, which was beneficial to the subsequent adhesion of the ITO film. After preheating, the glass substrate was transferred to the sputtering chamber, and an ITO target with a purity of 99.99% (indium tin oxide, In2O3:SnO2=90:10; purchased from Zhuzhou Torch Antai New Materials Co., Ltd.) was selected as the magnetron sputtering target. The working gas was argon with a purity of 99.999%, the argon flow rate was controlled to 100 sccm, and the vacuum degree was 1×10 -4Pa, sputtering power of 400W, sputtering speed of 1.5nm / min, a 100nm thick ITO film is plated on a glass substrate, then cooled to room temperature, and then annealed at 350℃ for 2h. During the annealing process, the crystal structure of the film will be further optimized, the resistivity of the film will be reduced, and its transparency will be improved. After annealing, a coated glass substrate is obtained;

[0063] Preparation of a protective layer: First, the coated glass substrate is ultrasonically cleaned in anhydrous ethanol, and then dried in a 50°C constant temperature drying oven for 12 hours. After completion, the modified coating prepared in Example 3 is sprayed on the coated side of the coated glass substrate to form a protective layer. The thickness of the protective layer is controlled at 100 nm. After spraying, it is placed in a 100°C constant temperature drying oven for curing for 100 minutes, and then stored in a dry environment for 24 hours. After completion, a touch screen glass panel is obtained.

[0064] Comparative Example 2

[0065] Comparative Example 2 is the control group of Example 5, in which the modified coating prepared in Example 2 in Example 5 is replaced by the modified coating prepared in Comparative Example 1, and the remaining raw materials, raw material amounts and preparation steps are consistent with Example 5, and finally a touch screen glass panel is obtained.

[0066] Comparative Example 3

[0067] Comparative Example 3 is the control group of Example 5, in which the protective layer preparation process in Example 5 is deleted, that is, the coated glass substrate prepared in Example 5 is used as the final prepared touch screen glass panel.

[0068] Test Example 1

[0069] The performance test was performed on the touch screen glass panels produced in Examples 4 to 6 and Comparative Examples 2 to 3. The performance test process is as follows, and the test results are shown in Table 1:

[0070] Performance testing process:

[0071] a. Light transmittance: Use GB530 integral light transmittance meter to test the light transmittance of the touch screen glass panel;

[0072] Testing process: Clean the touch screen glass panel, remove dust and stains on the surface, turn on the integral transmittance meter and calibrate it, put the calibration piece into the test port, adjust the parameters according to the instrument manual, so that the transmittance displayed is the known transmittance value of the calibration piece, then take out the calibration piece, place the touch screen glass panel vertically on the test port, ensure that the light passes vertically through the glass panel, and record the transmittance value displayed by the integral transmittance meter.

[0073] b. Hardness: Use Mineralab Mohs hardness tester to test the Mohs hardness of the touch screen glass panel;

[0074] Testing process: first fix one side of the protective layer of the touch screen glass panel on a horizontal surface to ensure that the test surface is flat. Start with talc with the lowest Mohs hardness of 1, and use a standard hardness mineral to perform a scratch test on the surface of one side of the protective layer of the glass panel at a pressure of 15N and a speed of 2mm / s. Observe whether there are scratches on the surface of the touch screen glass panel. If there are no scratches, replace the mineral with a higher hardness and continue testing until a mineral that can leave scratches on the surface of the touch screen glass panel is found. The Mohs hardness of the mineral is the hardness of the touch screen glass panel.

[0075] c. Contact angle: Refer to GB / T 30693-2014 "Measurement of water contact angle on plastic surface" to detect the contact angle of the touch screen glass panel;

[0076] Testing process: Clean one side of the protective layer of the touch screen glass panel and place it on the sample stage of the measuring instrument (German Kruss DSA100S contact angle tester), ensure that the surface is level, use a micro syringe to add 5μL of pure water / hexadecane (simulated oil) on the surface of the touch screen glass panel, observe the shape of the droplet through the optical system of the measuring instrument, and use the instrument software to measure the contact angle between the droplet and the surface of the touch screen glass panel, and record the value.

[0077] d. Anti-fingerprint performance: Use the German SITA surface cleanliness meter to test the anti-fingerprint performance of the touch screen glass panel;

[0078] Testing process: A surface cleanliness meter is used to measure the cleanliness of the protective layer of one side of the touch screen glass panel before and after the coating after the fingerprint is pressed, wherein ten test points are pressed on the protective layer of one side of the touch screen glass panel of each group of embodiments / comparative examples, and finally the RFU values ​​of the test points are measured. The larger the RFU value, the higher the surface pollutant content. The RFU values ​​of the ten test points of each group of embodiments / comparative examples are averaged.

[0079] e. Peel strength: Refer to GB / T 2790-1995 "Adhesive 180° Peel Strength Test Method Flexible Material to Rigid Material" to test the peel strength of the protective layer in the touch screen glass panel;

[0080] Testing process: Use a tensile testing machine, set a tensile speed of 20 mm / min, start the testing machine, and record the maximum tensile force during the peeling process of the protective layer from the touch screen glass panel. The peeling strength is calculated by dividing the maximum tensile force by the peeling width.

[0081] Table 1 Test results

[0082]

[0083] As can be seen from Table 1, the touch screen glass panels produced by Examples 4 to 6 of the present invention and Comparative Examples 2 to 3 all have excellent light transmittance and Mohs hardness. By comparing the data of Comparative Examples 2 to 3 and Example 5, it can be seen that the touch screen glass panel prepared by Example 5 of the present invention has excellent self-cleaning performance and anti-fingerprint performance. From the peel strength data of Example 5 and Comparative Example 2, it can be seen that the protective layer of the touch screen glass panel prepared by Example 5 of the present invention has excellent anti-peeling performance.

[0084] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.

[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A touch screen glass panel, characterized in that: including a glass substrate; An ITO thin film is coated on the surface of the glass substrate by magnetron sputtering to obtain a coated glass substrate; The surface of the coated glass substrate is coated with a modified coating to obtain a touch screen glass panel; The modified coating is prepared by the following steps: A1. Fill anhydrous ethanol with nitrogen for protection, then add 3-aminopropyltriethoxysilane and 2H,2H-perfluorooctanal thereto with stirring, add p-toluenesulfonic acid thereto after stirring and mixing, heat to 40-50° C., stir at constant temperature for 8-12 hours, cool to room temperature, remove ethanol to obtain a crude product, separate and purify the crude product by column chromatography, elute with eluent, and rotary evaporate to obtain fluorine-containing silane; A2. Mix tetraethyl silicate, 1,2-bistrimethoxysilylethane and 2-perfluorooctylethyl alcohol, stir and heat to 40-45°C, then add 36% hydrochloric acid solution by mass and stir to adjust the pH of the system to 4.5-5.

0. After completion, add pure water and fluorine-containing silane after mixing and stirring, heat to 50°C, stir at constant temperature for 12 hours, then distill under reduced pressure, add methyl-1,1,2,2-tetrafluoroethyl ether to dilute to a solid content of 3.5%-4.0%, then add dibutyltin diacetate and stir for 1-2 hours to obtain a modified coating.

2. The touch screen glass panel according to claim 1, characterized in that: The amount ratio of anhydrous ethanol, 3-aminopropyltriethoxysilane and 2H,2H-perfluorooctanal in A1 is 500mL:0.1mol:0.1-0.11mol; the amount of p-toluenesulfonic acid in A1 is 2-5mol% of the total molar amount of 3-aminopropyltriethoxysilane and 2H,2H-perfluorooctanal.

3. The touch screen glass panel according to claim 1, characterized in that: The column chromatography described in A1 uses a silica gel column; the eluent described in A1 is prepared by a volume ratio of n-hexane:ethyl acetate=5:

1.

4. The touch screen glass panel according to claim 1, characterized in that: The dosage ratio of tetraethyl silicate, 1,2-bistrimethoxysilylethane, 2-perfluorooctylethyl alcohol, pure water and fluorine-containing silane compound described in A2 is 1g:2.8~3.0g:10g:10mL:0.54~0.55g; the dosage of dibutyltin diacetate described in A2 is 0.5%~1.0% of the total mass of the mixed solution.

5. A method for manufacturing a touch screen glass panel according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Mix glass substrate raw materials and place them in a high-temperature furnace for melting. The furnace temperature is 1450-1540° C. and the melting time is 4-5 hours. After completion, a glass liquid is formed. The glass liquid is then clarified. The clarification temperature is 1550-1650° C. and the clarification time is 2-3 hours. After completion, a clarified glass liquid is obtained. The clarified glass liquid is floated on molten tin liquid. The tin liquid temperature is controlled at 1000-1100° C. and the time is controlled at 4-5 minutes. Under the action of gravity and surface tension, the clarified glass liquid is formed into a substrate-shaped glass. The substrate-shaped glass is then annealed and cooled to obtain a glass substrate. S2, subjecting the preheated glass substrate to magnetron sputtering coating, selecting an ITO target material with a purity of 99.99% as a target material, coating an ITO thin film on the glass substrate, cooling it to room temperature, and then annealing it at 320-350° C. for 1.5-2 hours to obtain a coated glass substrate; S3, spraying the modified coating on the coated side of the cleaned and dried coated glass substrate to form a protective layer, and then curing and drying to obtain a touch screen glass panel.

6. The method for manufacturing a touch screen glass panel according to claim 5, characterized in that: The glass substrate in S1 includes the following raw materials in parts by mass: 62-65 parts of SiO2, 10-15 parts of Na2O, 8-12 parts of Al2O3, 1-3 parts of B2O3, 2-5 parts of K2O, 4-5 parts of MgO, and 3-5 parts of CaO.

7. The method for manufacturing a touch screen glass panel according to claim 5, characterized in that: The temperature of the annealing treatment in S1 is 580-650° C., and the annealing time is 12 hours.

8. The method for manufacturing a touch screen glass panel according to claim 5, characterized in that: The conditions of magnetron sputtering described in S2 are as follows: the working gas is argon with a purity of 99.999%, the argon flow rate is controlled to be 10-100 sccm, and the vacuum degree is 1×10 -3 ~1×10 -4 Pa, the sputtering power is 300-400W, and the sputtering speed is 1.5nm / min.

9. The method for manufacturing a touch screen glass panel according to claim 5, characterized in that: The thickness of the ITO film in S2 is 100 nm.

10. The method for manufacturing a touch screen glass panel according to claim 5, characterized in that: The thickness of the protective layer in S3 is 50-100 nm.

Citation Information

Patent Citations

  • Modified AF coating material and preparation method and coating method thereof

    CN111621229A

  • Near-infrared high-transmittance coated glass and preparation method thereof

    CN116589201A